Relação entre sono e sistema imune: uma abordagem translacional em doenças dermatológicas - Albuquerque, Rachel Gimenes Rodrigues [UNIFESP] (2019)
Introduction: The skin is an organ with complex physiology, which includes from the defense against infectious agents to neuroendocrine functions. The study of dermatological diseases also depends on the investigation of the immune system communication within the central nervous system. In this context, we highlight the importance of sleep in the body homeostasis, including its participation on the imune function. Recently it has been demonstrated the importance of sleep in several autoimmune dermatological diseases. However, the sleep role in infectocontagious disease, which has dermatological manifestations, it is still nuclear. Objectives: To investigate the effects of chronic sleep fragmentation on L. major infection in resistante and suceptible strains of mice on the progression of leishmaniasis and cytokines production. To evaluate sleep pattern and subjective sleep quality, psychosomatic aspects and cytokines concentration in leprosy patients and controls. Methods: We used 84 mice (52 from C56BL/6 strain and 32 from BALB/c strain) submitted to L. major infection. Mice underwent a protocol of sleep fragmentation for 21 days after infection. Body weight and foot sweeling were measured from all mice. Blood samples, feet, spleen and lymphnodes were collected to assess parasite load, serum cytokines concentration and cytokines production in cultures of dendritic cells with T CD4+ cells. The clinical study enrolled 47 volunteers (15 controls and 32 leprosy patients) that underwent polysomnography, blood puncture to assess serum cytokines concentrations, subjective evaluations of sleep quality, excessive daytime sleepiness, fatigue, restless leg syndrome diagnosis, symptoms of anxiety and depression, quality of life and pain. Results: Sleep fragmentation did not affect body weight, foot swelling and parasite load. Sleep fragmented infected C57BL/6 mice presented lower concentrations of IL17 in the co-cultures of dendritic cells and T CD4+ cells. Sleep fragmented infected BALB/c had lower concentrations of IL-1α e IL-5. Patients with leprosy had lower socioeconomic status, demonstrated by lower educational level and manual labor. Alcohol comsumption were lower in this group when compared to controls. Most of patients were classified as multibacilar, with more patients from the forms borderline lepromatous and lepromatous. Incapacities were mostly observed in hands. Leprosy group had a higher sleep latency, awake index, apnea hypopnea index and dessaturation index when compared to controls. Also, a lower mininal saturation, worse quality of life, higher association to severe depressive symptoms and fatigue. Patients enrolled in leprosy reactions treatment with prednisone and thalidomide had higher concentrations of IFNγ and IL-17A, lower sleep latency and higher sleep efficiency when compared to those taking only prednisone. Conclusions: Sleep fragmentation protocol was not capable to affect the progression of leishmaniasis in resistant and susceptible mice strains. The differences found in cytokines concentrations are probably mainly due the presence of outliers. It is necessary to readequate our protocol, especially considering the amount of volume and number of parasites inoculated. Leprosy patients have alterations on sleep pattern, worse quality of life and daytime impairment. Also, reactions treatment may have an importante role on changes demonstrated by polysomnography and serum cytokines.